2013
DOI: 10.4236/as.2013.47a005
|View full text |Cite
|
Sign up to set email alerts
|

Medium effects on micropropagation and genetic stability of <i>Citrullus lanatus</i> oleaginous type

Abstract: To regenerate adventitious shoots from the cotyledon proximal parts of Citrullus lanatus (Thunb.) Matsum. and Nakai ssp. mucosospermus (Fursa) oleaginous type, different concentrations of MS mineral elements, sucrose, 6-benzylaminopurine (BAP) and agar were tested. Shoot induction proved to depend on the interaction between levels of sucrose, BAP and MS mineral elements in the medium. The medium containing 3/2 strength of MS mineral elements, 35 g/l sucrose and 1 mg/l BAP solidified with 6 g/l agar allowed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…On the other contarary, Gnamien et al (2013) tested different concentrations of MS mineral elements and BAP to regenerate adventitious shoots from the cotyledons of Citrullus lanatus. They found that the medium containing 3/2 strength of MS mineral elements and 1 mg/l BAP allowed the production of numerous shoots.…”
Section: Means With the Same Letter In The Same Column Are Not Signifmentioning
confidence: 99%
“…On the other contarary, Gnamien et al (2013) tested different concentrations of MS mineral elements and BAP to regenerate adventitious shoots from the cotyledons of Citrullus lanatus. They found that the medium containing 3/2 strength of MS mineral elements and 1 mg/l BAP allowed the production of numerous shoots.…”
Section: Means With the Same Letter In The Same Column Are Not Signifmentioning
confidence: 99%
“…For example, weaker salt medium such as WPM promoted the formation of axillary bud development in forest plant species (McCown and Sellmer, 1987) and it was probably due to lower concentration of salts and sucrose than those of B5 and MS (Bhatt and Dhar, 2004). In the other side, application of double strength MS medium resulted in increase the number of formed shoots compared to full strength MS (Gnamien et al, 2013).…”
Section: Introductionmentioning
confidence: 99%